DANA PERIMBANGAN DAN PEMBANGUNAN MANUSIA: SEBUAH BUKTI PENGUJIAN DARI PULAU KALIMANTAN - Evi Maria; Abdul Halim; Muhammad Luthfan (UNIVERSITAS INDRAPRASTA PGRI, 2021)
The purpose of this research is to investigate the relationship between fiscal balance funds and human development and also to see the behavior of budget use in the Kalimantan Island. This research uses panel data regression analysis using a sample of four provinces in Kalimantan Island with the observation year 2010-2016. The results of the study found partially the General Allocation Fund and the Special Allocation Fund had a positive influence on human development on the Kalimantan Island. Meanwhile, the Revenue Sharing Fund has no effect on human development on the Kalimantan Island. This is because the Kalimantan Island Revenue Sharing Fund experienced a significant decline in 2014-2016 and the use of the Revenue Sharing Fund from Natural Resources is limited by regulation on environmental sustainability. Simultaneously, fiscal balancing funds, namely General Allocation Funds, Special Allocation Funds, and Revenue Sharing Funds has an influence on human development on the Kalimantan Island. This research found that the implementation of decentralization in Indonesia made local governments tend to rely on Fiscal Balance Funds to finance human development programs in the regions.